INFLUENCE OF DESTINATION IMAGE AND CUSTOMER EXPERIENCE TO REVISIT INTENTION AT KAI’ SANTI GARDEN - Rompas, Fransisca; Saerang, David P.E.; Tumewu, Ferdinand J. (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: Destination Image is an important factor in the success of a destination. It contains the sum of impression of a destination. Customer experience contains the result of the interaction and what customer got from the destination using their sense, feel, think and act. The match between what is expected by customer and what is felt and got can make customer have intention to revisit and recommend the destination to other people because the feeling of satisfied. This research is aim to find out the influence of destination image and customer experience to revisit intention to Kai’ Santi Garden Woloan. This is a quantitative research and using Multiple Linear Regression. The population of this research is people who have visited Kai’ Santi Garden Woloan with 100 respondents as the sample size. This research showed that destination image and customer experience simultaneously influence revisit intention while partially, destination image have a significant influence to revisit intention and customer experience does not have a significant influence to revisit intention. Kai’ Santi Garden should reconsider about their price strategy, improve employees’ service and performance and facilities. Keywords: destination image, customer experience, revisit intention